Philosophical and methodological reflection on database capacity planning: a controllership standpoint (Journal of Information Systems and Technology Management, 2005)
This paper analyzes the capacity-planning process of database management systems focusing the theoretical decision models that considers the variables constraints that could be taken slightly and other variable constraints that are indispensable during upgrade. In order to proceed with the aforementioned, we assume that capacity planning decision, which considers the general corporate, technical, users and executive views aiming at prioritizing a measurable relative importance of the planning constraints is capable of giving more economic added-value decision elements to the management. Thus, the optimization multicriteria analysis leads us to infer upon the reasonableness of the decision taken in regard to implementing budgetary planning in moment of business uncertainties. Results of this study indicate that corporate strategic views in decision-taking processes some times override some technical, users and executive views as relating to capacity planning in information technology management environment.